New therapies for neurovascular bundles regeneration after radical prostatectomy: A narrative review on clinical studies - Rivero Belenchón, Inés; Gómez Rivas, Juan; Medina López, Rafael Antonio; Checcucci, Enrico; Taratkin, Mark; Puliatti, Stefano; Kowalewski, Karl-Friedrich; Cacciamani, Giovanni; Congregado Ruíz, Carmen Belén; Castro, Cristina; Enikeev, Dmitry; Abad-Lopez, Pablo; et al. (Frontiers in Urology, 2022)
Prostate cancer is the most common cancer amongst men, and one of its treatments in the localized stage is radical prostatectomy (RP). This technique achieves a high success rate regarding oncological results, but one of its main drawbacks are sexual disorders, especially erectile dysfunction, ranging from 14-90% of the cases. Therefore, surgery advancements in the last decade have been focused on minimizing the impact on patient’s functioning. Now is time for a step forward in the recovery of functional outcomes after RP. Bioengineering solutions such as stem-cell therapy and tissue engineering hold great opportunities for the treatment of all tissues and organs dysfunctions, which may help in neuroprotection and neuro-regeneration. Specifically, the use of Dehydrated human amnion/chorion membrane (dHACM) allografts and chitosan membranes (ChiMe) aims at reconstructing damaged neurovascular plexuses of the urogenital system to support erectile function recovery. Some research is being done on this topic, and promising results are emerging.